On Water Cu@g‐C3N4 Catalyzed Synthesis of NH‐1, 2, 3‐Triazoles via [2+3] Cycloadditions of Nitroolefins/Alkynes and Sodium Azide. Issue 23 (7th November 2018) - Payra, Soumen; Saha, Arijit; Banerjee, Subhash
Abstract: Here, we have reported fabrication of graphitic polymeric C3 N4 supported CuCl2 (Cu@g‐C3 N4 ) and characterized by powder X‐ray diffraction, field emission scanning electron microscopy, high resolution transmission electron microscopy, X‐ray photoelectron spectroscopy studies. An efficient and regioselective protocol for the on water synthesis of 4‐aryl‐ NH ‐1, 2, 3‐triazole derivatives via 1, 3‐diipolar cycloaddition reactions of nitroolefins/phenylacetylenes to sodium azide were demonstrated by using Cu@g‐C3 N4 as robust and reusable catalyst. Abstract : The tides of carbon nitride : Here, we have developed of graphitic polymeric C3 N4 supported CuCl2 (Cu@g‐C3 N4 ) material for efficient and regioselective on water synthesis of 4‐aryl‐ NH ‐1, 2, 3‐triazole derivatives via 1, 3‐diipolar cycloaddition reactions of nitroolefins/phenylacetylenes to sodium azide.